The autosomal Gsdf gene plays a role in male gonad development in Chinese tongue sole (Cynoglossus semilaevis). Issue 1 (December 2018) - Zhu, Ying; Meng, Liang; Xu, Wenteng; Cui, Zhongkai; Zhang, Nianwei; Guo, Hua; Wang, Na; Shao, Changwei; Chen, Songlin
Abstract Gsdf is a key gene for testicular differentiation in teleost. However, little is known about the function ofGsdf in Chinese tongue sole (Cynoglossus semilaevis ). In this study, we obtained the full-lengthGsdf gene (CS -Gsdf ), and functional characterization revealed its potential participation during germ cell differentiation in testes.CS -Gsdf transcription was predominantly detected in gonads, while the levels in testes were significantly higher than those in ovaries. During the different developmental stages in male gonads, the mRNA level was significantly upregulated at 86 dph, and a peak appeared at 120 dph; then, the level decreased at 1 and 2 yph.In situ hybridization revealed thatCS-Gsdf mRNA was mainly localized in the Sertoli cells, spermatogonia, and spermatids in mature testes. AfterCS-Gsdf knockdown in the male testes cell line by RNA interference, a series of sex-related genes was influenced, including several sex differentiation genes, CS-Wnt4a, CS-Cyp19a1a andCS-Star . Based on these data, we speculated thatCS-Gsdf may play a positive role in germ differentiation and proliferation via influencing genes related to sex differentiation.